The digital rights delusion : humans, machines and the technology of information - Monti, Andrea (New York: Routledge, 2023)
'This book examines the ever-increasing impact of technology on our lives and explores a range of legal and constitutional questions that this raises. It considers the extent to which concepts such as'cyberspace' and'digital rights' advance or undermine our understanding of this development and proposes a number of novel approaches to the effective protection of our rights in this rapidly evolving environment. Finally, it shows how the abuse of the adjective digital has demoted legal rights into subjective and individual claims. The work will be of particular interest to scholars of privacy, artificial intelligence, free speech, as well as policymakers and the general reader'--
Ain't no such thing as'cyberspace' -- The quest for digital rights -- Social networks and rights -- Encryption and rights -- AI, robots and (their?) rights -- Conclusions.
Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 6393/ Pemilihan Ketua Perpustakaan Undang-Undang/ CIP/ Areesh Education & Trading
Includes bibliographical references and index. (169-176 pages)
Keywords: Internet -- Law and legislation; Artificial intelligence -- Law and legislation; Digital media -- Law and legislation; Civil rights; Personality (Law); Technological innovations -- Law and legislation